The out of school literacy practices and semiotic resources of two grade 4 boys who excel at creative writing - Abdulla, Nabila (School of Education, 2017)
Previous socio-cultural research has shown the importance of creative writing and that children's creative writing is fuelled by their interests . It is believed that reading and writing is intimately connected and that those who can read well should be able to write well and vice versa. However, teachers have argued that those who do read tend to fill their writing with elements of popular culture, and those who read extensively aren't all capable of producing quality fictional writing either, as the skills and knowledge which they develop from reading don't necessarily translate into their writing. Through my teaching experiences I discovered a general negativity amongst South African teachers towards creative writing. Furthermore, the South African curriculum seems to provide little support for the advancement in creative writing as well. As a result I became interested in two of my learners, both boys, who excel at creative writing. Their narratives are rich in detail, contain exciting plots, and are generally entertaining and engaging reads. Both boys are avid readers as well. I questioned what contributed to their ability to produce excellent narratives as reading could not be the only factor. As I was aware of their in-school practices I decided it would be beneficial to examine their out of school literacy practices and semiotic resources and whether they affect or contribute towards their creative writing. I developed a case study based on home visits, interviews and collecting artefacts. I discovered that family social practices underpin many of the out of school literacy practices and that reading, drawing and play featured as contributing practices towards their creative writing. Furthermore through Bakhtin's notion of appropriation and Kristeva's notion of intertextuality, I analysed how popular culture featured prominently in the boy's writing as a means of expressing not only their own individual interests, but as a resource for identity work, representing the ways in which they see themselves in their official world as well. This research hopes to encourage further research into children's creative writing in order to change the way in which writing is viewed in the South African curriculum and to chal lenge teacher's perceptions on what constitutes "good" creative writing among primary school children.